Pengaruh Interaksi Mahasiswa dengan Dosen Penutur Asli Bahasa Mandarin terhadap Kemampuan Berbicara - Hesi Rahma Novita; Lukluk Ul Muyassaroh; Rosyidah (Singular: Journal of Pedagogical Language, Literature, and Cultural Studies, 2025)
Mandarin Chinese is considered one of the most influential languages in the world due to its significant role across various do-mains, including education, business, and culture. However, learners, particularly university students, often face challenges in mastering pronunciation, tones, and the complex Hanzi characters. Direct interaction with native-speaking instructors has proven to be an effective method for enhancing students' speaking abilities. This study aims to examine the impact of student interactions with native Mandarin-speaking lecturers on their speaking proficiency. Employing a quantitative approach, the study utilized Pearson correlation analysis and simple linear regression. The findings revealed a Pearson correlation coefficient of 0.943 and a significance level of <0.05 in the regression analysis, indicating a strong, positive, and significant relationship between the two variables. The more frequent and intensive the interaction, the greater the improvement observed in students' vocabulary mastery, pronunciation accuracy, intonation, and confidence. Furthermore, native-speaking instructors offer authentic learning experiences and broader cultural insights. Therefore, the involvement of native Mandarin-speaking lecturers is crucial in enhancing students’ Mandarin speaking skills.